Optimizing heart failure pathways to enhance patient care: the Program to Optimize Heart Failure Patient Pathways (PRO‐HF) - Patwala, Ashish; Barker, Diane; Da Costa, Antoine; Bayard, Geoffrey; Brunner‐La Rocca, Hans‐Peter; Fontes‐Carvalho, Ricardo; De la Fuente, Luis; Goralski, Marc; Mahon, Niall G.; Roque, David; Santos, Mario; Yousef, Zaheer; et al. (ESC Heart Failure, 2024)
Aims Many European healthcare providers struggle to adopt multidisciplinary, integrated care pathways for people with heart failure (HF) as recommended by the European Society of Cardiology. PRO‐HF (Program to Optimize Heart Failure Patient Pathways) was developed to help clinicians identify strengths, gaps, and shortcomings in their HF pathways and support tailored interventions to optimize pathways and enhance patient care. We report initial findings from baseline assessments of HF pathway characteristics and challenges from 10 hospitals in six European countries (France, Ireland, Portugal, Spain, The Netherlands, and United Kingdom). Methods and results Baseline assessments were holistic appraisals of full HF services to calibrate current status and development needs and assist management teams in prioritizing improvement projects. Assessments were performed using a comprehensive checklist of measures covering the HF patient journey from diagnosis to ongoing follow‐up. These included a digital survey sent to full HF care teams and one‐to‐one interviews. The digital survey focused on four key areas (HF outpatient clinic; remote patient management; efficient device implantation and inpatient pathways; and network maximization) and 16 dimensions of excellence. Priority areas and themes for action identified in baseline assessments were (i) provision of HF specialist care; (ii) data capture and analysis; (iii) institutional care protocols; (iv) hospital‐wide strategies; and (v) multidisciplinary teams (MDTs). Suboptimal specialist care of emergency inpatients was an issue at all hospitals and prioritized at 8/10. Availability and accessibility of data on patients, activities, and outcomes was an issue at all hospitals and prioritized by 4/10. A lack of clear protocols, templates, and tools for some HF activities created variability in patient care (e.g., HF specialist consultations, diagnostic testing, follow‐up appointments, medications, and device eligibility) and inefficient use of clinician time. This made it difficult to initiate new technologies (e.g., remote patient monitoring) due to the risk of overburdening staff. MDTs were frequently understaffed. Multiple interventions were identified to address gaps and shortcomings that could be tailored to specific needs of individual hospitals (e.g., inpatient pathway optimization, creation/optimization of HF outpatient clinics, development of an HF performance dashboard, enhancement of protocol adherence, streamlining cardiac resynchronisation therapy pathways, and MDT coordination). Conclusions PRO‐HF provides a valuable opportunity to identify gaps and significant shortcomings in HF pathways in European hospitals. Preliminary findings from hospitals that have initiated suggested changes to address these challenges are encouraging, though longer‐term follow‐up from more hospitals is needed to confirm the impact of PRO‐HF on HF pathway optimization and patient care.